Optimization Parameters of Durian Peel-Based Activated Carbon Using Response Surface Methodology (RSM) - Nury, Dennis Farina; Kurniawati, Intan Wahyuning; Manurung, Martin Sugiarto; Luthfi, Muhammad Zulfikar; Iqbal, Muhammad Nasyarudin (Journal of Chemical Process Engineering, 2024)
Durian peel is one of the agricultural wastes that has not been utilised optimally and has the potential to be used as an alternative to biomass-based activated carbon. This study was conducted to study the optimisation process of making activated carbon from durian peel using H3PO4 activator. The optimisation process was carried out using Response Surface Methodology (RSM) to optimise the variables that affect the quality of activated carbon using the Box-Behnken method. The variables used were 20% v/v, 25% v/v, and 30% v/v H3PO4 concentrations, activation time of 12 hours, 24 hours, and 36 hours, weight ratio of activated carbon to H3PO4 activator 1:2 m/v, 1:3 m/v, and 1:4 m/v. The optimization using RSM method results showed an iodine absorption capacity of 790.139 mg/g obtained under the following conditions, H3PO4 concentration of 30% v/v, activation time of 34.78 hours, and weight ratio of activated carbon to H3PO4 activator of 1:4 m/v. Activated carbon from durian peel with optimum conditions obtained surface area value of 2.407 × 10-11 m2 and activated carbon diameter of 4.878 μm using Scanning Electron Microscopy (SEM) analysis test